Agricultural Challenges in the Brazilian Semiarid Region (Sustainability in Debate, 2013)
This gallery is one of the results of fieldwork conducted in the Brazilian semi-arid region between2011 and 2013, in the states of Bahia, Pernambuco, Rio Grande do Norte, Piauí and Ceará.Around 1,140 family farmers were interviewed.